Saving preferences of households in Poland - Krupa, Dorota; Walczak, Damian; Chojnacka, Ewa (Copernican Journal of Finance & Accounting, 2013)
The purpose of this article is to present the savings’ preferences of households in Poland. Households in Poland invest primarily in deposits made in Polish zloties. Their primary motivation is saving for flats and houses and in the second motivation is saving for durable goods. For the purpose of the analysis authors used the data published by National Bank of Poland and statistical data published in the Social Diagnosis 2011 report.